2003
DOI: 10.1139/z03-109
|View full text |Cite
|
Sign up to set email alerts
|

Winter habitat use by female caribou in relation to wildland fires in interior Alaska

Abstract: The role of wildland fire in the winter habitat use of caribou (Rangifer tarandus) has long been debated. Fire has been viewed as detrimental to caribou because it destroys the slow-growing climax forage lichens that caribou utilize in winter. Other researchers argued that caribou were not reliant on lichens and that fire may be beneficial, even in the short term. We evaluated the distribution of caribou relative to recent fires (<50 years old) within the current winter range of the Nelchina caribou herd in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
101
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(115 citation statements)
references
References 19 publications
14
101
0
Order By: Relevance
“…The presence of fires (burns) and deforestation within a site was found to be negatively associated with woodland caribou occurrence (Table 1). Woodland caribou have been reported to avoid disturbed forests, both those that have been harvested and have undergone fire activities (Darby & Duquette, 1986;Rettie & Messier, 1998;Joly et al, 2003). The disturbance of forest through timber harvesting and fire activities is known to alter predator-prey interactions as it can facilitate apparent competition (Wittmer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of fires (burns) and deforestation within a site was found to be negatively associated with woodland caribou occurrence (Table 1). Woodland caribou have been reported to avoid disturbed forests, both those that have been harvested and have undergone fire activities (Darby & Duquette, 1986;Rettie & Messier, 1998;Joly et al, 2003). The disturbance of forest through timber harvesting and fire activities is known to alter predator-prey interactions as it can facilitate apparent competition (Wittmer et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, woodland caribou tend to show strong preference for areas with water bodies, wetlands, and peatlands alongside hilly areas to cope with heat stress (Racey, 2005), avoid predators, and ease of movement in winter (O'Brien et al, 2006;Fortin et al, 2008;Courbin et al, 2014). Linear features (e.g., roads, railways, trails, utility lines), forest developments (e.g., timber harvest), and natural disturbances (e.g., forest fires, blow downs) fragment the boreal forest and negatively impact woodland caribou (Rettie & Messier, 1998;James & Stuart-Smith, 2000;Joly et al, 2003;Fortin et al, 2008;Courbin et al, 2014). These disturbances alter the composition and structure of forests by changing mature forests to early successional stages (Joly et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a major disturbance such as fire or heavy grazing pressure, the recovery of lichen mats may take a lengthy period of time (~45 kg ha" yr" , Auclair 1985) preventing their use by caribou for up to 50 years (Scotter 1964, Kelsall 1968, Klein 1982, Joly et al 2003, 2007a, Jandt et al 2008.…”
Section: Chapter -Thesis Introduction Contextmentioning
confidence: 99%
“…Most literature suggests that caribou prefer mature, forested habitat with abundant mat-forming lichens (Scotter 1964, Kelsall 1968, Klein 1982. These authors believe that fire has a negative effect on caribou habitat, due to the slow recovery time of terricolous (ground-dwelling) lichens that form the majority of a caribou's diet during winter (60 -80%; Scotter 1964, Kelsall 1968, Klein 1982, Fleischman 1990, Joly et al 2003. Although researchers have noted that caribou sometimes forage in recently burned habitats Rowe 1975, Joly et al 2003), they are mostly observed to avoid these areas in favour of older, lichen-rich communities (>55 years of age; Klein 1982, Thomas et al 1996, Joly et al 2003, 2009a.…”
Section: Chapter -Thesis Introduction Contextmentioning
confidence: 99%